2020
DOI: 10.2139/ssrn.3638748
|View full text |Cite
|
Sign up to set email alerts
|

Metadichol®, A Novel Nano Lipid Formulation that Inhibits SARS-CoV-2 and a Multitude of Pathological Viruses in Vitro

Abstract: Background New pathogenic virus outbreaks, occurring with increasing regularity, are leading us to explore novel approaches, which will reduce the reliance on time-consuming vaccine modes to halt the outbreaks. The requirement is to nd a universal approach to disarm any new and as yet unknown viruses as they appear. A promising approach could be targeting lipid membranes, which are common to all viruses and bacteria. The ongoing pandemic of severe acute respiratory syndrome-coronavirus 2 (SARS-COV-2) has rea r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…To date, there have been a few in silico attempts to find small molecule inhibitors of the interaction between ACE2 and spike S1-RBD. Cao et al, de novo designed sequences of a few amino acid . Raghavan et al, reported ACE2 inhibition by Metadichol . Chowdhury et al, reported the hACE2 inhibitory activity of 15 antiviral peptides containing aromatic nonpolar, and polar amino acids along with their SAR studies.…”
mentioning
confidence: 99%
“…To date, there have been a few in silico attempts to find small molecule inhibitors of the interaction between ACE2 and spike S1-RBD. Cao et al, de novo designed sequences of a few amino acid . Raghavan et al, reported ACE2 inhibition by Metadichol . Chowdhury et al, reported the hACE2 inhibitory activity of 15 antiviral peptides containing aromatic nonpolar, and polar amino acids along with their SAR studies.…”
mentioning
confidence: 99%